Aggressive in pursuit : the life of Justice Emmett Hall - Vaughan, Frederick (Osgoode Society for Canadian Legal History., 2004)
Few people have had a greater impact on the lives of Canadians than the late Supreme Court judge Justice Emmett Hall. At the forefront of several important judgements in the 1960s and 70s - such as Truscott and Calder - Hall is perhaps best known for his role in the adoption of universal health care at the federal level in 1968. Based on extensive interviews with Hall and people who knew him, Frederick Vaughan's Aggressive in Pursuit tells Hall's remarkable story. Born in Quebec in 1898 and raised in Saskatchewan, Hall had a long and distinguished career as a lawyer. In 1957, former law school classmate Prime Minister John Diefenbaker appointed Hall to the Saskatchewan Court of Queen's Bench, and four years later to the office of Chief Justice of Saskatchewan. In 1963, Diefenbaker elevated Hall to the Supreme Court of Canada, where he took up the task of universal health care and showed himself to be an aggressive defender of native causes. Aggressive in Pursuit traces Hall's career from his earliest days of private practice in Saskatchewan to the end of his career, and death, in 1994. It shows how one prairie lawyer made a difference in the life of Canada.